"Hama"? Reduced pronunciations in non-native natural speech obstruct high-school students' comprehension at lower processing levels. (September 2021) - Wanrooij, Karin; Raijmakers, Maartje E.J.
Highlights: Dutch high-school students fail to understand German naturally reduced speech. Non-native reductions obstruct perception also when controlling for speech rate. The reductions hamper at least acoustic–phonetic analysis and bottom-up processing. Second-language training requires more experience with naturally reduced variants. Abstract: Native speakers 'reduce' their pronunciations, i.e., they shorten and merge words. For instance, German native speakers may say "hama" for "haben wir" ('have-we'). We examined to what extent such reductions are problematic for adolescent learners of a second language, after four years of high-school training; and whether the problems can be related to inadequate bottom-up and top-down processing. For this, 39 Dutch and 38 German adolescents heard either reduced or unreduced German full phrases and part-phrases (phrase-intelligibility task) and words (lexical decision task). The results show that (1) Learners perceive non-native reduced speech less accurately than unreduced speech and also judge it as less intelligible; (2) This reduced-form disadvantage occurs separately from factors such as speech rate, orthography and voice; (3) The disadvantage for non-native listeners is substantial and larger than that in native listeners. Therefore, it probably reflects a lack of experience with reduced (i.e., real-life) speech; and (4) Non-native reductions induce at least inadequate bottom-up processing in learners, and may make top-down processing less accessible. We interpret the findings as supporting the idea that experience with variants (here: reduced variants) is necessary to strengthen linguistic (word) representations.